L'Assommoir. - Zola, Emile (Floating Press, 1877)
Regarded by critics as one of the highest pinnacles of achievement in Emile Zola's literary career, L'Assommoir (best translated as "the cheap liquor store") offers an unflinching look at alcoholism among the working class in nineteenth-century France. Part of a larger, 20-volume story cycle that spanned Zola's entire career, L'Assommoir was the novel that initially propelled the writer to fame and fortune.